Detection of copper, cadmium, manganese, lead, and zinc content in milled rice using microwave plasma atomic emission spectroscopy - Ramos, Nerissa C.; Lamorena, Rheo B. (2021)
"This study validated a new method that is not only rapid and cost-effective but also accurate and reliable in the detection of trace metals in rice. The microwave plasma atomic emission spectroscopy (MP-AES) method of tracing elements in rice was validated to quantitatively measure the copper (Cu), manganese (Mn), zinc (Zn), cadmium (Cd), and lead (Pb). Validation that involved precision, accuracy, linearity and dynamic working range, standard addition for matrix effects, limit of detection (LOD), and limit of quantitation (LOQ) showed that the MP-AES method was comparable with flame atomic absorption spectroscopy (FAAS) data"-Title page.
Includes bibliographical references.
Keywords: Microwave plasmas; Trace elements